Islam, MENA Region and Research Methods - Abdelkader, Deina (Araucaria, 2019)
The distinction between normative and objective knowledge and how social scientist imagine that their research is solely built on objectivity is currently being challenged especially in the political science field. If we take culture as an example and more specifically the question of identity and identity politics in the Middle East, we will find that the current modus operandi in political science research is distancing itself from objective knowledge because of the increased focus in the field on quantification. Whether one analyzes the work of Telhami on Identity in the Middle East, or Lynch’s “The Arab Uprisings Explained”, one will find that they all reflect on the academic conundrum that the field is facing.